Determinants and Consequences of Student Learning Satisfaction During Covid-19 Pandemic - Saragih, Arfah Habib; Adwie, Joansyah; Hendrawan, Adang (Jurnal Ilmiah Akuntansi dan Bisnis, 2021)
This study examines the effect of student perception in online learning on student satisfaction and its impact on student learning performance and intention to use in the future. The regression analysis method was used based on the survey results from 157 students. Results indicate that students' perceptions of online learning had a positive effect on student satisfaction, intention to use, and student learning performance. Further, student satisfaction has a positive effect on student learning performance but does not affect the intention to use. The implications for lecturers, students, and faculties are also discussed. Keywords :  student perception, online learning, student satisfaction,   student performance, intention to use, covid-19 pandemic